COMPARATIVE CHARACTERISTICS OF PIGMENT COMPOSITION FROM RAW MATERIALS AND OIL EXTRACT OF NETTLE LEAVES - O. V. Trineeva; A. I. Slivkin (Разработка и регистрация лекарственных средств)
Spectral characteristics of leaves and oil extract of a nettle by a two-blast furnace in various solvents are investigated. The characteristic strips of ab-sorption caused by presence carotenoids and chlorophylls are revealed. The method of spectrophotometry certain a content of studied pigments in leaves of a nettle by a two-blast furnace and an oil extract. The method bidimentional TLC leads division of pigments of investigated objects. The general characteristic zones detected as on the chromatograms of raw material, and an oil extract are revealed. Chromatographic profiles of pigments of each type of raw material and the oil extract received on its basis, has a unequal appearance that it is possible to use with a view of their standardization, using a method of «prints of fingers» biologically active substances on the chromatograms. Content of studied biologically active substances in an oil extract on two orders below in comparison with leaves that is maybe connected with features of allocation the given pigments fat vegetable oils. The choice of the best type of plates for division of pigments of leaves and an oil extract of a nettle by a two-blast furnace in a thin layer is lead.